HUBUNGAN TINGKAT PENDIDIKAN BERBASIS ISLAM ANGGOTA KARANG TARUNA DENGAN KEPEDULIAN SOSIAL - Hawin, Moch (Universitas Ahmad Dahlan, 2019)
Islam Islamic religious education is a conscious and planned effort in preparing students to get to know, and understand, appreciate, to believe in the history of Islam, accompanied by demands to respect adherents of Islam in relation to harmony between religious communities to realize national unity and unity. Caring is a basic value and attitude to pay attention and act proactively to the conditions or circumstances around us. This study aims to determine and analyze the relationship between the level of Islamic-based education with the social care of members of the village of Karang Taruna. The population in this study were all members of the Kebontemu village of Karang Taruna Karang, while the study sample was taken by simple random sampling method with a total of 30 members of Karang Taruna. The results of the research hypothesis and test on the relationship found that there is a positive relationship between the level of Islamic-based education on social care that exists in the members of the Karang Taruna Kebontemu village